iPSC line derived from a Bloom syndrome patient retains an increased disease-specific sister-chromatid exchange activity. - Vincent Gatinois; Romain Desprat; Fabienne Becker; Lydiane Pichard; Florence Bernex; Bertrand Isidor; Franck Pellestor; Jean-Marc Lemaitre (Stem Cell Research, 2020)
Bloom syndrome is characterized by severe pre- and postnatal growth deficiency, immune abnormalities, sensitivity to sunlight, insulin resistance, and a high risk for many cancers that occur at an early age. The diagnosis is established on characteristic clinical features and/or presence of biallelic pathogenic variants in the BLM gene. An increased frequency of sister-chromatid exchanges is also observed and can be useful to diagnose BS patients with weak or no clinical features. For the first time, we derived an induced pluripotent cell line from a Bloom syndrome patient retaining the specific sister-chromatid exchange feature as a unique tool to model the pathology.